PDCA Cycle Method implementation in Industries: A Systematic Literature Review - Deni Ahmad Taufik (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
The industry's development increasingly makes businesses competitive by increasing technical knowledge and improving systems, both internally and externally. The PDCA (Plan, Do, Check, Action) cycle is a quality management system used as a continuous improvement tool widely used in industries. The PDCA is a continuous improvement tool that is widely used in industries. The PDCA cycle begins with small to check possible effects on systems and eventually progresses to larger and more specific improvements. The implementation of the PDCA method results in solving the problems of qualitative and quantitative data problems that have been widely applied in industries for continuous improvement and as a work pattern in improving a process or system in an organization and increasing productivity. The methodology used in this research is the literature review research paper was published in 2010-2020. The literature review describes the relationship between thinking and gaps in theoretical and practical thinking about applying the PDCA method and the successful implementation in industries as a contribution to further research.